Single Stage Correction of Rectovestibular Fistula (Journal of Paediatric Surgeons of Bangladesh, 2014)
Introduction: The aim of this study was to determine the feasibility, safety, cost effectiveness and functional outcome between single stage and multiple stage operation of anorectal malformation (ARM) with rectovestibular fistula (RVF).Materials & Methods: This interventional study was conducted on 40 female children born with ARM with RVF from July 2007 to June 2009 in the Department of Pediatric Surgery, Dhaka Medical College Hospital. Their age range was from 3 months to 7 years. Anterior sagittal anorectoplasty (ASARP) was done as definitive treatment of RVF. 20 out of 40 patients underwent single stage procedure and the rest underwent multiple stage procedure. Good preoperative bowel preparation and postoperative wound care were ensured for optimum outcome.Results: Mean operating time was 70 minutes in single stage and 80 minutes in multi stage definitive procedure.  Average hospital stay was 10 days in single stage procedure where as 22-24 days in multi stage procedure. Partial perineal wound dehiscence occurred in two patients with single stage procedure and one patient with multi stage procedure. Wound infection was seen in two patients of single stage and also two patients of multi stage procedures. Fecal continence was good in all patients older than 3 years. Average number of bowel movement was 2-3 times daily in older patients and 2-4 in younger patients. Constipation developed in three patients with multiple stage procedure and in two patients with single stage procedure. Both groups were managed conservatively for all complications. In Dhaka Medical College Hospital, treatment cost is mostly free, so we could not compare this cost but the incidental expenses in single stage treatment was Tk. 10,000.00 and Tk. 30,000.00 in multistage treatment in three settings.Conclusion: Adequate preoperative bowel preparation, good surgical skill, proper analgesia and postoperative wound care remain the key factors to produce a cost effective excellent outcome of single stage correction of RVF.DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19523